Exploring the exoproteome of the parasitic nematode Anisakis simplex (s. s.) and its impact on the human host – an in vitro cross-talk proteomic approach - Stryiński, Robert; Fiedorowicz, Ewa; Mateos, Jesús; Andronowska, Aneta; Łopieńska-Biernat, Elżbieta; Carrera, Mónica (Frontiers in Immunology, 2025)
IntroductionAnisakis simplex sensu stricto (s. s.) is one of the most widespread parasitic nematodes of marine organisms, with humans as accidental hosts. While many studies have explored nematode biology and host interactions, the role of extracellular vesicles (EVs) as signaling molecules in parasitic nematodes is less understood.Materials and methodsTherefore, the proteins present in the EVs of A. simplex (s. s.) (Anis-EVs) were identified. In addition, a cross-talk proteomic approach was used to identify differentially regulated proteins (DRPs) in the proteome of the human intestinal epithelial cell line (Caco-2) co-cultured with L3 larvae of A. simplex (s. s.) or directly exposed to two concentrations (low or high) of Anis-EVs. In addition, DRPs were identified in the proteome of A. simplex (s. s.) larvae affected by co-culture with Caco-2. To achieve this goal, the shotgun proteomics method based on isobaric mass labeling (via tandem mass tags; TMT) was used with a combination of nano high-performance liquid chromatography (nLC) coupled with an LTQ-Orbitrap Elite mass spectrometer. In addition, ELISA assays were used to demonstrate if Caco-2 respond to A. simplex (s. s.) larvae and Anis-EVs with significant changes in selected cytokines secretion.ResultsThe results of this study indicate the anti-inflammatory character of Anis-EVs in relation to Caco-2. At the same time, direct treatment with Anis-EVs resulted in more significant changes in the Caco-2 proteome than co-culture with L3 larvae.DiscussionThe results obtained should lead to a better understanding of the molecular mechanisms underlying the development of A. simplex (s. s.) infection in humans and will complement the existing knowledge on the role of EVs in host-parasite communication.